The tragedy of King Lear - Shakespeare, William, 1564-1616 (Mumbai : Wilco International, 2023)
Presents Shakespeare's tragedy in which an English king foolishly splits his kingdom between the two daughters plotting his doom and disinherits his favorite for speaking out against him.
Keywords: Lear, -- King of England (Legendary character) -- Drama; Inheritance and succession -- Drama